2010
DOI: 10.1093/hmg/ddq073
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneous nuclear ribonucleoprotein-R is necessary for axonal β-actin mRNA translocation in spinal motor neurons

Abstract: Axonal transport and translation of beta-actin mRNA plays an important role for axonal growth and presynaptic differentiation in many neurons including hippocampal, cortical and spinal motor neurons. Several beta-actin mRNA-binding and transport proteins have been identified, including ZBP1, ZBP2 and hnRNP-R. hnRNP-R has been found as an interaction partner of the survival motor neuron protein that is deficient in spinal muscular atrophy. Little is known about the function of hnRNP-R in axonal beta-actin trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
99
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 59 publications
3
99
0
Order By: Relevance
“…Intriguingly, CG17838 is the Drosophila homolog of two closely related vertebrate RNA-binding proteins, HNRNPR and SYNCRIP, both of which bind to SMN in a yeast two-hybrid assay (31) and localize to mRNAcontaining granules that are transported in cultured neurons (27,31,42). Because both SMN and HNRNPR affect localization of mRNA in axons (43,44), this could have profound consequences on local translation in neurons (44).…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, CG17838 is the Drosophila homolog of two closely related vertebrate RNA-binding proteins, HNRNPR and SYNCRIP, both of which bind to SMN in a yeast two-hybrid assay (31) and localize to mRNAcontaining granules that are transported in cultured neurons (27,31,42). Because both SMN and HNRNPR affect localization of mRNA in axons (43,44), this could have profound consequences on local translation in neurons (44).…”
Section: Discussionmentioning
confidence: 99%
“…SMN2 genomic DNA contains a few nucleotide mutations compared with SMN1 (21,22). Full-length SMN protein functions in the U snRNP assembly/disassembly, as well as in the β-actin mRNA transport in neurons (23,24). However, the mutations in SMN2 pre-mRNA cause predominantly skipping of exon 7, which produces SMNΔ7, a truncated and less stable protein with reduced self-oligomerization activity.…”
mentioning
confidence: 99%
“…However, issues such as which transcripts are most sensitive to SMN deficiency and whether their splicing defects lead to SMA pathogenesis remain to be investigated. In addition, it has been shown that SMN forms RNA granules with other RNA-binding proteins such as hnRNP R to deliver -actin mRNA in motor axons (Glinka, et al, 2010;Rossoll, et al, 2003). A recent report showed that clustering of Cav2.2 calcium channels is impaired in axonal growth cones of SMA animals, and such a defect can be restored by rescue of SMN expression (Jablonka, et al, 2007).…”
Section: How Does Smn Deficiency Cause Sma Pathogenesismentioning
confidence: 99%